Effect of a school-linked life skills intervention on adolescents' sexual and reproductive health skills in Guji zone, Ethiopia (CRT)—A generalized linear model - Godana, Gobena; Garoma, Silesh; Ayers, Nicola; Abera, Muluembet (Frontiers in Public Health, 2023)
Background Although appropriate life skills are recognized as a fundamental right for adolescents and a critical component of health policy, they are often overlooked and rarely researched in pastoral communities. Life skills encompass the ability to adopt positive behaviors, which enable individuals to effectively deal with the demands and challenges of everyday life. This study aimed to evaluate the effectiveness of a school-linked life skills intervention program on adolescents' sexual and reproductive health skills in the pastoral community of Guji zone. Methods A two-arm cluster randomized control trial with a pretest-posttest experimental design was conducted, involving the intervention group (N = 375) and the control group (N = 384). This study assessed the effect of a school-linked adolescent-friendly life skills intervention in comparison to the usual RH curriculum, used as a control arm. Pretest-posttest and posttest-posttest scores of the control group and trial groups were compared, and the data were collected using 27 self-administered questions. The collected data were analyzed using paired-sample independent t-tests and a generalized linear model to examine the relationship between the dependent and independent variables. Results Data were collected from 759 adolescents in 15 intervention and 15 control clusters. The findings have shown that the proportion of mean life skills score was significantly higher in the intervention clusters than controls [(375) 70.49% vs. (384) 62.25%, P < 0.001 95% CI (0.06 and 0.1)]. Adolescents who were trained in school-linked life skills (β = 1.915, 95% CI: 1.411–2.418), were confident to make safe and informed decisions (β = 1.999, 95% CI: 1.562–2.436), and had life skills to deal with SRH issues (β = 1.66, 95% CI: 1.233–2.087) were significantly correlated with predicting the relevant life skills. The proportion of adolescents with SRH life skills increased from 384 (52%) at baseline to 375 (70%) at end line in the intervention group compared to 384 (60.31%) at baseline to 384 (62.31%) in control arms, respectively. Conclusions The implementation of a school-linked life skills intervention program proved to have a significant effect on SRH life skills development. Furthermore, individual-level and behavioral-level variables were significant in explaining variability in life skills development within the pastoral community. Therefore, we recommend scaling up this intervention in all high schools. Trial registration Trial registration PACTR202107905622610, registered on 16 July 2021.